Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1158/0008-5472.can-14-3000
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic Anhydrase IX Promotes Myeloid-Derived Suppressor Cell Mobilization and Establishment of a Metastatic Niche by Stimulating G-CSF Production

Abstract: The mobilization of bone marrow-derived cells (BMDC) to distant tissues before the arrival of disseminated tumor cells has been shown preclinically to facilitate metastasis through the establishment of metastatic niches. Primary tumor hypoxia has been demonstrated to play a pivotal role in the production of chemokines and cytokines responsible for the mobilization of these BMDCs, especially in breast cancer. Carbonic anhydrase IX (CAIX, CA9) expression is highly upregulated in hypoxic breast cancer cells throu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
90
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(99 citation statements)
references
References 54 publications
6
90
0
Order By: Relevance
“…For hepatocellular carcinomas, hypoxia and TGF-β induce LOXL2 in the primary tumor and in patient sera, thereby increasing tissue stiffness and promoting cancer cell adhesion and metastasis (61). As an indirect mechanism, hypoxia-induced expression of carbonic anhydrase IX in breast cancer cells leads to the secretion of G-CSF, which mobilizes granulocytic MDSCs to pre-metastatic lungs and promotes metastasis (62). The effects of other types of stresses in the primary tumors, such as nutrient deprivation, on the establishment of a pre-metastatic niche are yet to be identified.…”
Section: Traits Of a Pre-metastatic Nichementioning
confidence: 99%
See 1 more Smart Citation
“…For hepatocellular carcinomas, hypoxia and TGF-β induce LOXL2 in the primary tumor and in patient sera, thereby increasing tissue stiffness and promoting cancer cell adhesion and metastasis (61). As an indirect mechanism, hypoxia-induced expression of carbonic anhydrase IX in breast cancer cells leads to the secretion of G-CSF, which mobilizes granulocytic MDSCs to pre-metastatic lungs and promotes metastasis (62). The effects of other types of stresses in the primary tumors, such as nutrient deprivation, on the establishment of a pre-metastatic niche are yet to be identified.…”
Section: Traits Of a Pre-metastatic Nichementioning
confidence: 99%
“…A thorough list of these factors and their effects on pre-metastatic niche has been summarized (8). More recent work has shown that factors secreted by hypoxic tumor cells, including LOX, LOXL2, and G-CSF, direct a pro-metastatic niche reprogramming (6062). LOXL2 has also been shown to collaborate with E47 to induce EMT and increase the secretion of GM-CSF to recruit BMDCs to pre-metastatic lungs (26).…”
Section: Tumor-derived Formation Of a Pre-metastatic Nichementioning
confidence: 99%
“…The bicarbonate goes back into the cell through bicarbonate transporters and balances the intracellular pH as alkaline, which is favourable for the cell's survival. The protons acidify the extracellular space, thus facilitating the tumour's migratory and invasive behaviour [45][46][47]. CAIX expression and activity also facilitates the production of Granulocytecolony stimulating factor (G-CSF),which is in turn required for the transportation of granulocytic Myeloid-derived Suppressor Cells (MDSC) to the metastatic niche-an environment that promotes metastasis.…”
Section: The Tumour Microenvironment and Hypoxiamentioning
confidence: 99%
“…CAIX expression is also required to stimulate NF-κB activity and G-CSF production mediated through hypoxia. The hypoxia-mediated NF-κB activity is triggered by a decrease in the pH level of the culture as well as hypoxia-induced glycolytic activity in the cancer cells [46,[48][49][50]. The hypoxic areas of tumours usually have lower levels of extracellular pH due to increased metabolic activity [45].…”
Section: The Tumour Microenvironment and Hypoxiamentioning
confidence: 99%
“…7 Potential roles of such cells may include enhancing vascular recovery as well as modulating immune reactivity or possibly enhancing metastasis. 8,9 High levels of neutrophils in the circulation and the tumour have also been associated with poor treatment outcome in cancers following irradiation. [10][11][12] In this article, I will review some of the old literature concerning tumour response to radiation treatment and relate this to current concepts about the role of the microenvironment in tumour response to radiation treatment.…”
Section: Introductionmentioning
confidence: 99%